T cells exacerbate Lyme borreliosis in TLR2-deficient mice - Lasky, Carrie E.; Pratt, Carmela L.; Hilliard, Kinsey A.; Jones, Jacob J.; Brown, Charles R. (Frontiers in Immunology, 2016)
Infection of humans with the spirochete, Borrelia burgdorferi, causes Lyme borreliosis and can lead to clinical manifestations such as arthritis, carditis, and neurological conditions. Experimental infection of mice recapitulates many of these symptoms and serves as a model system for the investigation of disease pathogenesis and immunity. Innate immunity is known to drive the development of Lyme arthritis and carditis, but the mechanisms driving this response remain unclear. Innate immune cells recognize B. burgdorferi surface lipoproteins primarily via toll-like receptor (TLR)2; however, previous work has demonstrated TLR2−/− mice had exacerbated disease and increased bacterial burden. We demonstrate increased CD4 and CD8 T cell infiltrates in B. burgdorferi-infected joints and hearts of C3H TLR2−/− mice. In vivo depletion of either CD4 or CD8 T cells reduced Borrelia-induced joint swelling and lowered tissue spirochete burden, whereas depletion of CD8 T cells alone reduced disease severity scores. Exacerbation of Lyme arthritis correlated with increased production of CXCL9 by synoviocytes, and this was reduced with CD8 T cell depletion. These results demonstrate T cells can exacerbate Lyme disease pathogenesis and prolong disease resolution possibly through dysregulation of inflammatory responses and inhibition of bacterial clearance.